Opsonic monoclonal antibodies enhance phagocytic killing activity and clearance of Mycobacterium tuberculosis from blood in a quantitative qPCR mouse model. Issue 9 (September 2019) - Sei, Clara J.; Shey, Bong-Akee; Schuman, Richard F.; Rikhi, Nimisha; Muema, Kevin; Rodriguez, John D.; Daum, Luke T.; Fourie, P. Bernard; Fischer, Gerald W.
Abstract: Background: Patients with impaired immunity often have rapid progression of tuberculosis (TB) which can lead to highly lethal Mycobacterium tuberculosis (MTB) sepsis. Opsonic monoclonal antibodies (MABs) directed against MTB that enhance phagocytic killing activity and clearance of MTB from blood may be useful to enhance TB immunity. Methods: BALB/c mice were immunized with ethanol-killed MTB (EK-MTB) and MABs were produced and screened by ELISA for binding to killed and live Mycobacterium smegmatis (SMEG) and MTB. MAB opsonophagocytic killing activity (OPKA) was examined using SMEG with HL60 and U-937 cells and MTB with U-937 cells. Clearance of MTB from blood was evaluated in Institute of Cancer Research (ICR) mice given opsonic anti-MTB MABs or saline (control) 24 h prior to intravenous infusion with 10 8 CFUs gamma-irradiated MTB (HN878). MTB levels in murine blood collected 0.25, 4 and 24 h post-challenge were assessed by qPCR. MAB binding to peptidoglycan (PGN) was examined by ELISA using PGN cell wall mixture and ultra-pure PGN. Results: Two MABs (GG9 and JG7) bound to killed and live SMEG and MTB (susceptible and resistant), and promoted OPKA with live MTB. MAB JG7 significantly enhanced OPKA of MTB. Both MABs significantly enhanced clearance of killed MTB from murine blood at 4 and 24 h as measured by qPCR. These opsonic MABs bound to PGN, a major cell wall constituent. Conclusions: Anti-MTB MABs that promote bactericidal phagocytic activity of MTB and enhance clearance of killed MTB from the blood, may offer an immunotherapeutic approach for treatment of MTB bacteremia or sepsis, and augment treatment of multi-drug resistant (MDR) or extensively drug resistant (XDR) TB.